2020
DOI: 10.1002/aws2.1193
|View full text |Cite
|
Sign up to set email alerts
|

Persistent contaminants of emerging concern in ozone‐biofiltration systems: Analysis from multiple studies

Abstract: Water quality, in combination with design and operational data collected from multiple studies, was assessed to benchmark the performance of ozone‐biologically active filtration in reuse applications. A total of 149 contaminants of emerging concern, representative of multiple categories and chemical structures, were prioritized and systematically compared to elucidate apparent differences in removal capabilities as affected by multiple factors such as influent water matrix, ozone‐to‐organic carbon ratio, empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…During the sampling events, O 3 :TOC ratio setpoints ranged between 0.8 and 1.3, corresponding to an ozone dose range of 5.0–8.6 mg/L. Studies show that, although ozone is effective in oxidizing PFAAs (Crone et al, 2019; Glover et al, 2018; Schröder & Meesters, 2005), it may increase the concentration of targeted PFAAs by oxidizing precursors (Dickenson et al, 2015; Sari et al, 2020). PFBS increased by an average of 31% after ozonation.…”
Section: Resultsmentioning
confidence: 99%
“…During the sampling events, O 3 :TOC ratio setpoints ranged between 0.8 and 1.3, corresponding to an ozone dose range of 5.0–8.6 mg/L. Studies show that, although ozone is effective in oxidizing PFAAs (Crone et al, 2019; Glover et al, 2018; Schröder & Meesters, 2005), it may increase the concentration of targeted PFAAs by oxidizing precursors (Dickenson et al, 2015; Sari et al, 2020). PFBS increased by an average of 31% after ozonation.…”
Section: Resultsmentioning
confidence: 99%
“…Even though there are reports on the efficient removal of microplastics by WWTPs, some microplastics are present in the effluent, requiring the development of microplastic‐targeted treatment processes (Magni et al, 2019; Sun et al, 2019). It was found that ozonation in the common O 3 /BAC treatment train could not remove the flame retardant and plasticizer tris(2‐chloroethyl)phosphate (TCEP), and the removal relies on biofiltration (Sari et al, 2020). A study on the removal of emerging contaminants by the treatment train of sand/anthracite filter followed by BAC showed that even though TCEP was low in concentration, but it persisted in the effluent (Fu et al, 2019).…”
Section: Removal Of Recently Emerging Contaminant By Biofiltration Systemmentioning
confidence: 99%
“…A recent data‐mining study (Sari et al, 2020) on the removal of emerging contaminants by O 3 /biological active filtration (BAF) also reported that ozonation was not effective for PFAS removal, and the removal should be mainly by adsorption, in which the effectiveness probably relies on the media condition used (e.g., virgin, regenerated, or exhausted). Compared to conventional biodegradation, BAC should have greater potential for PFAS biodegradation since the carbon‐based media could promote more microbial diversity in biofilms (Vignola et al, 2018).…”
Section: Removal Of Recently Emerging Contaminant By Biofiltration Systemmentioning
confidence: 99%
“…For ozonation and biological media filtration (BMF), however the water matrix characteristics play a crucial role in the disinfection effectiveness which has limited the use of indicators such as ozone dose and CT, applied elsewhere in water treatment. [8][9][10] This limitation has impeded the formal attribution of LRV credits to ozonation and BMF for wastewater in many jurisdictions. LRV credits have been awarded to postozonation at Melbourne Water's Eastern Treatment Plant (ETP) (the subject of this study) on the basis of CT disinfection.…”
Section: Introductionmentioning
confidence: 99%